Sosialisasi Kandungan Zat Gizi Bolu Kukus Berbasis Daun Katuk dalam Memperlancar ASI sebagai Makanan Selingan Ibu Menyusui Pascabencana kepada Masyarakat Kelurahan Duyu, Kota Palu - Fitrasyah, Siti Ika; Ariani, Ariani; Ekawati Lukman, Try Nur; Putri, Linda Ayu Rizka; Rakhman, Aulia; Maharani, Dhea Putri; Sari, Sartika Purnama (Universitas Tadulako, 2024)
Breast milk is the best food for babies and has many benefits for feeding babies and mothers. The nutritional content is used for the development of the body's immune system and the baby's brain. One of the obstacles in providing breast milk is the lack of milk production after giving birth. Using katuk leaf juice as a snack product is believed to increase secretion and facilitate breast milk. So far, many boiled katuk leaves are still eaten as a vegetable due to a need for knowledge and skills in making steamed sponge cakes for breastfeeding mothers. Duyu Village. This community service activity aims to increase participants' knowledge of katuk leaf juice-based sponge cake as an alternative snack. The benefits achieved in activity are that participants can learn how to make steamed sponge cake based on katuk leaf juice and can increase the production of breast milk secretion for breastfeeding mothers. The methods that will be used in this training activity include the lecture method, used to explain material about how to make steamed sponge cake; practice method, used to practice how to make steamed sponge cake; Discussion method, carried out after the training activity is completed to find out the participants' responses. This training activity included pregnant and breastfeeding mothers in Duyu Village, Palu City. The type of product being socialized is steamed sponge cake based on katuk leaves. The location of the service is Duyu Village, Palu City. Community Service Activities will be held on August 19 2023.